Factors in the suboptimum performance of rural water supply systems in the Ethiopian highlands - Tilahun, Seifu A.; Tigabu, A.D.; Tarekegne, T.M.; Addisie, Meseret B.; Beyene, H.A.; Alemeyehu, Z.A.; Ayele, M.; Collick, A.S.; Steenhuis, Tammo S. (International Livestock Research Institute, 2013)
Access to safe drinking water services in the Ethiopian Highlands is one of lowest worldwide due to failure of water supply services shortly after construction. Over hundred water supply systems were surveyed to find the underlying causes of failure and poor performance throughout the Amhara Regional State. The results show generally that systems with decision-making power at the community level during design and construction remained working longer than when the decisions were made by a central authority. In addition, the sustainability was better for water systems that were farther away from alternative water resources and contributed more cash and labour. The results of this study of the importance of decision-making at the local level in contrast to the central authority is directly applicable to the introduction of rain water management systems as shown by earlier efforts of installing rain water harvesting systems in the Ethiopian highlands.